2015
DOI: 10.5194/amtd-8-3399-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A method to derive the Site Atmospheric State Best Estimate (SASBE) of ozone profiles from radiosonde and passive microwave data

Abstract: Abstract. We present a method to derive the site atmospheric state best estimate (SASBE) of the ozone profile combining brightness temperature spectra around the 142 GHz absorption line of ozone measured by the microwave radiometer SOMORA and ozone profiles measured by the radiosonde (RS). The SASBE ozone profile is obtained using the radiosonde ozone profile as a priori information in an optimal estimation retrieval of the SOMORA radiometer. The resulting ozone profile ranges from ground up to 65 km altitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…4a turns southward before reaching the vortex erosion region above the Caspian Sea. Figures 4a and 5a are appropriate for visualizing the surf zone of the midlatitude stratosphere in winter (McIntyre and Palmer, 1984). Figures 4a and 5a also show the anti-correlation of the spatial distributions of ozone and water vapour in the mid-stratosphere since stratospheric polar air is rich in water vapour and poor in ozone.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…4a turns southward before reaching the vortex erosion region above the Caspian Sea. Figures 4a and 5a are appropriate for visualizing the surf zone of the midlatitude stratosphere in winter (McIntyre and Palmer, 1984). Figures 4a and 5a also show the anti-correlation of the spatial distributions of ozone and water vapour in the mid-stratosphere since stratospheric polar air is rich in water vapour and poor in ozone.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the retrieved ozone values at these altitudes are primarily based on the measured line spectrum. For technical details, measurement principle and retrieval procedure of the instruments; see, for example, Moreira et al (2015), Peter (1997), Hocke et al (2007), Maillard Barras et al (2009Barras et al ( , 2015 and references included therein. An intercomparison study of Hocke et al (2007) indicated that the relative differences between SOMORA and Aura/MLS are less than 10 %.…”
Section: The Microwave Radiometers Gromos and Somoramentioning
confidence: 99%
See 1 more Smart Citation
“…Most overpasses of a satellite during the years 1997-2012 will lead to a close collocation in time, given the hourly resolution of the SASBE. Using individual radiosonde measurements rather than a SASBE can minimise the number of collocations significantly, as was the case in Calbet et al (2017), who analysed differences between the Infrared Atmospheric Sounding Interferometer (IASI, Siméoni et al, 1997) and GRUAN radiosonde profiles, but was limited to using data from one GRUAN site only. If the satellite data product, i.e.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, the retrieved ozone values at these altitudes are primarily based on the measured line spectrum. For technical details, measurement principle and retrieval procedure of the instruments; see, for example, Moreira et al (2015), Peter (1997), Hocke et al (2007), Maillard Barras et al (2009Barras et al ( , 2015 and references included therein. An intercomparison study of Hocke et al (2007) (Moreira et al, 2015;Studer et al, 2014Studer et al, , 2012Keckhut et al, 2010;Flury et al, 2009;Steinbrecht et al, 2009;Hocke et al, 2007;Dumitru et al, 2006).…”
Section: Introductionmentioning
confidence: 99%